LÓPEZ VALERO, A., ENCABO FERNÁNDEZ, E., JEREZ MARTÍNEZ, I. y HERNÁNDEZ DELGADO, L. (2021). "Literatura infantil y lectura dialógica. La formación de educadores desde la investigación". Barcelona: Editorial Octaedro, 140 páginas, ISBN 978- 84-18819-40-7 - Aurora Martínez Ezquerro (Universidad de La Rioja, 2022)
LÓPEZ VALERO, A., ENCABO FERNÁNDEZ, E., JEREZ MARTÍNEZ, I. y HERNÁNDEZ DELGADO, L. (2021). Literatura infantil y lectura dialógica. La formación de educadores desde la investigación. Barcelona: Editorial Octaedro, 140 páginas, ISBN 978-84-18819-40-7